(untitled) (Aporia, 2020)
In this essay, I will identify the grounds on which Locke justifies the right of resistance in the Second Treatise of Government (1690). My argument unfolds in two parts: In the first part, I will introduce some basic concepts (section 2) that Locke appeals to in order to run his argument for the right of resistance (section 3). The second part consists of a criticism by John Mabbott (1973), which turns on the distinction between political society and government (section 4), and my interpretation of Locke that evades it successfully (section 5).